The homegarden agroforestry system in Sandakan - Muhammad Razali Mohammad (2005)
Sabah has unique social life of 50 multiethnic groups; about 30 are indigenous who display wide cultural diversity practices. In relation to this the social life of these multiethnic groups has believed have a interrelationship with the homegarden practices that have been implemented since long time ago in their everyday life. So that, an early documented information on these practices needs to carry out. Therefore, the objectives of this study were to investigate the involvement of Sandakan District villagers in practicing the homegarden Agroforestry (AF) system with comparing six ethnics group i.e Jawa, Bugis, Tidung, Dusun, Sungai and Chinese. This study also looks into component combination of AF system, structure and identifies gender participation between ethnic groups. Seventy-two heads of households were choosing through random sampling. Data obtained were mainly analyzed through cross tabulations and frequencies tables; Spearmen R test and Chi-square test were performed to determine relationship and relatedness while Kruskal Wallis test was conducted to determine differences in structure and component combination between six ethnic groups. Results from Spearmen R test showed Significant relationship in component combination; 84.7% (overall total) were preferred Agrosilvopastural as component combination. Whilst in homegarden structure indicated insignificant relationship. Nevertheless, Kruskal Wallis test also showed insignificant differences between six ethnic groups in component combination and structure at 95% Level of Confidence (LoC). Thus, male accounted 86% as head of homegarden practices and other family members as giving help. Hence, similar studies need to develop in whole of Sabah to obtain a comprehensive information of all Sabah's ethnic groups in homegarden practices.